Tourism and Hospitality Training: Hallmark of the Culinary and Hospitality Management Institute - Williams, Donna M. (International Journal of Bahamian Studies, 2014)
This paper traces the evolution of tourism and hospitality training in The Bahamas over the last 40 years, focusing on stakeholders, pioneers, partnerships, organizational structures, programs, and other key factors that have contributed to the establishment and operation of the Culinary and Hospitality Management Institute at the College of The Bahamas